Azide-functionalized lanthanide-based metal-organic frameworks showing selective CO2 gas adsorption and postsynthetic cavity expansion - Ganguly, Sumi; Pachfule, Pradip; Bala, Sukhen; Goswami, Arijit; Bhattacharya, Sudeshna; Mondal, Raju (Inorganic Chemistry, 2013)
We report herein selective CO2 gas adsorption by two azide-functionalized lanthanide-based metal-organic frameworks (MOFs). This work also demonstrates that azide-functionalized MOFs can be used for postsynthetic cavity expansion, further corroborated by enhanced gas-sorption data.